Managing urban dynamics in old industrial cities - Lessons learned on revitalising inner-city industrial sites in six European case studies - Tanja Tötzer; Ute Gigler (European Regional Science Association (ERSA), 2005)
For many European cities structural economic changes have a tremendous impact on the city's image, labour force and the spatial and (socio-) economic framework. City administrations are struggling with industries becoming obsolete or moving elsewhere and leaving derelict and often contaminated sites in the core of the city. The cities have to cope with the consequences, such as social decay, joblessness and environmental contamination. Revitalising derelict inner city sites is essential for a sustainable urban development, because it improves the image of the site and its neighbourhoods, it helps reduce sprawl on the urban fringe and it enhances environmental quality. Although cities could derive multiple benefits from reusing those sites, a revitalisation is afflicted with many risks and uncertainties and therefore represents a major challenge for a city. This paper presents experiences gained and lessons learned in six different revitalisation case studies in Gothenburg (S), Liverpool (GB), Lisbon (P), Berlin (D), Steyr (A) and Barcelona (ES). The research was conducted within the EU project MASURIN (Management of Sustainable Revitalisation of Urban Industrial Sites, EVK4-CT-2001-00054). The cases researched demonstrate that certain key factors and approaches need to be in place that allow cities to redevelop old industrial sites in a sustainable manner. In complex systems such as cities local circumstances, stakeholders' views and the types of organisations involved play a major role. The cases illustrate that open communication, trust and cooperation between public and private stakeholders accelerate the revitalisation process and lead to a balanced and mutually accepted outcome. Following a holistic concept and a vision, but staying flexible throughout the process helps create resilient structures, which strengthen the urban fabric and essentially contribute to a sustainable development of the whole city.
Keywords: 330